Penerapan Metode Critical Incident Pada Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Pada Siswa SMA Negeri 8 Medan - Nelly Natalia Sitanggang (KOLONI, 2023)
This study aims to determine whether the critical incident model is effective in improving students' mathematical problem solving skills in the linear subject matter program of SMA Negeri 8 Medan T.P 2022/2023. The instruments used are tests and observations. The test used was a written test in the form of a description of 3 tests consisting of 5 items for Cycle I, 5 items for Cycle II and 5 items for Cycle III. While the observation was carried out by observing student learning activities, the teacher's ability to manage learning as well as testing the ability to solve problems on learning. From the results of classroom action research it was successful in obtaining an increase in mathematical problem solving abilities. The effectiveness of learning mathematics is seen from the completeness of student learning in the first cycle of 10 students (27.03%), in the second cycle of 24 students (64.86%), and in the third cycle of 33 students (89.19%). The effectiveness of learning mathematics in terms of student learning activities, there is an increase in the percentage of activeness. In cycle I it was 53% and it was in the quite active category, in cycle II it was 78% and it was in the active category and in cycle III it was 86% and it was in the very active category. The effectiveness of learning mathematics in terms of the teacher's ability to manage learning after learning is carried out using the critical incident method, maximizing motivation for students, the involvement of students in learning groups can make students have an increase in the percentage in the first cycle of 55% and is in a fairly positive category, in cycle II of 71% and is in the good category and in cycle III is 94% and is in the very good category. students in terms of the percentage increase in cycle I was 65% and was in the less positive category, in cycle II was 80% and how much was in the positive category, and in cycle III was 95% and was in the very positive category. Based on the details of the research results above, it can be interpreted that learning uses the critical incident method for students of SMA Negeri 8 Medan in the 2022/2023 academic year on the subject of linear programming Keywords: Critical Incident, ability, problem-based learning model, problem solving, Mathematics